2014
DOI: 10.3109/0142159x.2014.970988
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety education to change medical students' attitudes and sense of responsibility

Abstract: Patient safety education effectively shifted students' attitudes towards systems-based thinking and increased their sense of collective responsibility. Strategies for improving superior-subordinate communication within a hierarchical culture should be added to the patient safety curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 20 publications
0
37
0
1
Order By: Relevance
“…After training, students increasingly attributed errors to system dysfunction and reported more selfconfidence in speaking up about colleagues' errors. However, due to the hierarchical culture, students still described difficulties communicating with senior doctors (Roh, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…After training, students increasingly attributed errors to system dysfunction and reported more selfconfidence in speaking up about colleagues' errors. However, due to the hierarchical culture, students still described difficulties communicating with senior doctors (Roh, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…one of the aims of implementing education on patient safety is developing awareness of the possibility of adverse events and the role of healthcare professionals in causing them. A study conducted in 2015 revealed that students' understanding, attitudes and sense of responsibility regarding patient safety improved after education (19).…”
Section: Methodsmentioning
confidence: 99%
“…We welcome the study by Roh et al (2015) demonstrating an improvement in thirdyear medical students' concepts of patient safety following the implementation of a structured patient safety educational programme (Roh, Park et al 2015). For maximal impact, a longitudinal model should be used in patient safety education so that undergraduate education translates into sustained tangible improvement in patient safety behaviour at graduate level.…”
mentioning
confidence: 99%
“…Such reporting bias poses an important challenge to healthcare organisations, since it probably affects the types of events that are highlighted to risk managers (Mitchell, Schuster et al 2015) and frustrates organisational learning. Though educational interventions, such as the one described in this study, provide one way of addressing this problem (Roh, Park et al 2015), efforts should also focus on ensuring that senior medical students and doctors-intraining feel safe to engage in the incident reporting process and that they recognise it as an important feature of collective responsibility. Case-based reflective learning from real-life patient safety incidents may enhance the benefits of incident reporting.…”
mentioning
confidence: 99%
See 1 more Smart Citation